Reaction severity to oral food challenge to milk is unpredictable: a caveat for clinical practice - Tosca, Maria Angela; Naso, Matteo; Schiavetti, Irene; Ciprandi, Giorgio (Acta Biomedica Atenei Parmensis, 2024)
Background Cow’s milk allergic (CMA) is common in infancy and early childhood; its work-up also is demanding. Oral food challenge (OFC) represents the gold-standard for diagnosis, but it may be dangerous. The present study aimed to identify possible risk factors predictive of severe reactions in clinical practice. Methods The study retrospectively evaluated data concerning children with positive OFC. The study evaluated detailed clinical history, including comorbidity, reactions’ characteristics, specific IgE to milk and its molecular components, and cumulative allergen dose. Results This study included 30 children (9 females and 21 males, mean age 89 months); 22 developed mild clinical reactions, four moderate, and four severe. There was no risk factor predictive of severe reaction. Conclusions This study emphasized the unpredictability of anaphylaxis during the OFC procedure, as no predictive and reasonable risk factors could rule out a severe reaction with absolute certainty. Consequently, OFC should be performed only at third-level pediatric allergy centers.